Characterization of a FOXG1:TLE1 transcriptional network in glioblastoma‐initiating cells. Issue 6 (27th April 2018) - Dali, Rola; Verginelli, Federica; Pramatarova, Albena; Sladek, Robert; Stifani, Stefano
Abstract : Glioblastoma (GBM) is the most common and deadly malignant brain cancer of glial cell origin, with a median patient survival of less than 20 months. Transcription factors FOXG1 and TLE1 promote GBM propagation by supporting maintenance of brain tumour‐initiating cells (BTICs) with stem‐like properties. Here, we characterize FOXG1 and TLE1 target genes in GBM patient‐derived BTICs using ChIP‐Seq and RNA‐Seq approaches. These studies identify 150 direct FOXG1 targets, several of which are also TLE1 targets, involved in cell proliferation, differentiation, survival, chemotaxis and angiogenesis. Negative regulators of NOTCH signalling, including CHAC1, are among the transcriptional repression targets of FOXG1:TLE1 complexes, suggesting a crosstalk between FOXG1:TLE1 and NOTCH‐mediated pathways in GBM. These results provide previously unavailable insight into the transcriptional programs underlying the tumour‐promoting functions of FOXG1:TLE1 in GBM. Abstract : Transcription factors FOXG1 and TLE1 promote glioblastoma (GBM) propagation. Here, we characterize FOXG1 and TLE1 target genes in GBM patient‐derived brain tumour‐initiating cells using ChIP‐Seq and RNA‐Seq approaches. These studies identify 150 direct FOXG1 targets, several of which are also TLE1 targets, involved in cell proliferation, differentiation, survival, chemotaxis and angiogenesis.